Quantitative mechanical assessment of the whole prostate gland ex vivo using dynamic instrumented palpation. (December 2017) - Hammer, Steven J; Good, Daniel W; Scanlan, Paul; Palacio-Torralba, Javier; Phipps, Simon; Stewart, Grant D; Shu, Will; Chen, Yuhang; McNeill, S Alan; Reuben, Robert L
An instrumented palpation sensor, designed for measuring the dynamic modulus of tissue in vivo, has been developed and trialled on ex vivo whole prostate glands. The sensor consists of a flexible membrane sensor/actuator with an embedded strain gauge and is actuated using a dynamically varying airflow at frequencies of 1 and 5 Hz. The device was calibrated using an indentation stiffness measurement rig and gelatine samples with a range of static modulus similar to that reported in the literature for prostate tissue. The glands were removed from patients with diagnosed prostate cancer scheduled for radical prostatectomy, and the stiffness was measured within 30 min of surgical removal. Each prostate was later examined histologically in a column immediately below each indentation point and graded into one of the four groups; normal, benign prostatic hyperplasia, cancerous and mixed cancer and benign prostatic hyperplasia. In total, 11 prostates were assessed using multiple point probing, and the complex modulus at 1 and 5 Hz was calculated on a point-by-point basis. The device yielded values of quasi-static modulus of 15 ± 0.5 kPa and dynamic modulus of 20 ± 0.5 kPa for whole prostates, and a sensitivity of up to 80% with slightly lower specificity was achieved on diagnosis of prostate cancer using a combination of mechanical measures. This assessment did not take into account some obvious factors such as edge effects, overlap and clinical significance of the cancer, all of which would improve performance. The device, as currently configured, is immediately deployable in vivo. A number of improvements are also identified which could improve the sensitivity and specificity in future embodiments of the probe.